SEMIOTIC REVIEW OF VERBAL LITERATURE OF RIWOK KERINCI - Nazurty, N (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2016)
Riwok verbal literature is a customary speech text delivered at the ceremonial feast of Sko. This study aims to interpret the expressions contained in the Riwok text through Semiotic Review. This study is a qualitative study using semiotic approach. Semiotic approach used to assess the meaning of the phrase in the text of verbal literature Riwok is based on semiotic theory of Charles Sanders Peirce, namely the triangular theory of meaning or meaning triangle which consists of three main elements, namely the sign, object, and interpretant. Signs, according to Peirce, consists of symbol (signs created from agreement), Icon (sign created from physical representation) and Index (sign created from cause-effect relationships). The results of the study found that in in the expression of Riwok text there are icon, index, and symbol signs. The signs were found in all Riwok texts. Based on the analysis of Riwok text, semiotic signs most commonly found is a sign of symbol. Symbols are found in the phrase which states the requirements for being an indigenous leader, a phrase which states the behavior of leaders, the phrase which states the roles, duties, and functions of traditional leaders, as well as the phrase stating customary sanctions.